PENGARUH MODEL PEMBELAJARAN TALKING STICK TERHADAP KETERAMPILAN SOSIAL SISWA PADA MATA PELAJARAN IPAS KELAS IV SEKOLAH DASAR - Khoirul Hidayati; Fajar Nur Yasin; Hikmah Luqiyah Kartikasari (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This research is motivated by the low social skills of fourth grade students at SDN Banjarbendo Sidoarjo because the learning process of the subject of science is still dominated by conventional lecture methods, thus making students tend to be passive, less courageous to express opinions, and difficult to work together. Therefore, this study aims to determine the effect of the talking stick learning model on students' social skills in the subject of science in grade IV of elementary school. This study uses a quantitative approach of the Quasi Experiment type with a Non-Equivalent Control Group Design. The research sample consists of two classes, namely class IV A as an experimental class consisting of 24 students and class IV B as a control class consisting of 25 students. Data collection techniques using questionnaires in the form of pretest posttest and observation. Data analysis was carried out through normality tests, homogeneity tests, and hypothesis tests using Independent Sample t-Test. The results showed that the implementation of the talking stick learning model had a positive effect on students' social skills. Students in the experimental class demonstrated greater improvement in social skills than those in the control class after participating in learning activities using the talking stick model. These findings indicate that the talking stick learning model is effective in improving students' social skills in elementary school science and social studies (IPAS) learning. Thus, the talking stick learning model is effective in improving students' social skills in the science subject on the unique habits of the people around me in grade IV elementary school. ABSTRAK Penelitian ini dilatar belakangi oleh rendahnya keterampilan sosial siswa kelas IV di SDN Banjarbendo Sidoarjo karena proses pembelajaran mata pelajaran IPAS masih didominasi oleh metode ceramah konvensional, sehingga membuat siswa cenderung pasif, kurang berani berpendapat, dan sulit bekerja sama. Oleh karena itu, penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran talking stick terhadap keterampilan sosial siswa pada mata pelajaran IPAS kelas IV sekolah dasar. Penelitian ini menggunakan pendekatan kuantitatif berjenis Eksperimen Semu (Quasi Experimental) dengan desain Non-Equivalent Control Group Design. Sampel penelitian terdiri atas dua kelas, yaitu kelas IV A sebagai kelas eksperimen yang berjumlah 24 siswa dan kelas IV B sebagai kelas kontrol yang berjumlah 25 siswa. Teknik pengumpulan data menggunakan angket berupa pretest posttest dan observasi. Analisis data dilakukan melalui uji normalitas, uji homogenitas, dan uji hipotesis menggunakan Independent Sample t-Test. Hasil penelitian menunjukkan bahwa penerapan model pembelajaran talking stick memberikan pengaruh positif terhadap keterampilan sosial siswa. Siswa pada kelas eksperimen menunjukkan peningkatan keterampilan sosial yang lebih baik dibandingkan dengan siswa pada kelas kontrol setelah mengikuti proses pembelajaran menggunakan model talking stick. Temuan tersebut membuktikan bahwa model pembelajaran talking stick efektif dalam meningkatkan keterampilan sosial siswa pada mata pelajaran IPAS. Dengan demikian, model pembelajaran talking stick efektif digunakan untuk meningkatkan keterampilan sosial siswa pada mata pelajaran IPAS materi keunikan kebiasaaan masyarakat di sekitarku kelas IV sekolah dasar.